Tracking Results in Agriculture and Rural Development in Less-Than-Ideal Conditions : A Sourcebook of Indicators for Monitoring and Evaluation - Global Donor Platform for Rural Development (Global Donor Platform for Rural Development, 2012)
The purpose of this sourcebook is to pull together into a single document a collection of common sense tips and recommendations based on actual practices and experience around the world. The sourcebook aims first and foremost to help strengthen Monitoring and Evaluation (M&E) capacity at the national and sub-national levels, and to ensure a consistency of approach and methodology so that, at the global level, sufficient reliable and timely information can be accessed from the different countries and used to make cross-country comparisons and to calculate development indicators at the global level. The sourcebook is specifically targeted towards countries where conditions are less-than-ideal, particularly with respect to the availability of relevant information. The sourcebook also shows how a service delivery approach can be used to select indicators which can generate useful, easy-to-measure early outcome measures. It suggests that greater use be made of qualitative indicators, such as access, use and satisfaction. The sourcebook devotes considerable attention to the need for a strong statistical infrastructure and reviews the range of different statistical instruments available.